Damage Assessment Method of Reinforcement Concrete Building By Fuzzy Theory - Jon Hyon Hui; Song Yong IL; Kim JI Yon (International Journal of Architecture and Urbanism, 2022)
As reinforcement concrete building is composition material which reinforcement bar and concrete work together, effect factors concerned with its damage are countlessly much and interrelationship between them is also very complex and indefiniteness. Until now many researches about the damage assessment of a building has been performed but the problem accounting correctly damage of the reinforcement concrete building by connecting several of damage factors has not yet been solved. In research a method accounting damage of reinforcement concrete building in the fuzzy integral way in consideration of fuzzy property existing in the damage assessment system of it has been newly suggested.